Higher resistance training volume offsets muscle hypertrophy nonresponsiveness in older individuals - Lixandrão, Manoel E.; Bamman, Marcas; Vechin, Felipe C.; Conceicao, Miguel S.; Telles, Guilherme; Longobardi, Igor; Damas, Felipe; Lavin, Kaleen M.; Drummer, Devin J.; McAdam, Jeremy S.; Dungan, Cory M.; Leitão, Alice E.; et al. (Journal of applied physiology (1985), 2024)
Using a within-subject unilateral design, we demonstrated that increasing resistance training (RT) volume may be a simple, effective strategy to improve muscle hypertrophy and strength gains among older adults who do not respond to low-volume RT. In addition, it could most likely be used to further improve hypertrophic outcomes in responders. The magnitude of muscle hypertrophy in response to resistance training (RT) is highly variable between individuals (response heterogeneity). Manipulations in RT variables may modulate RT-related response heterogeneity; yet, this remains to be determined. Using a within-subject unilateral design, we aimed to investigate the effects of RT volume manipulation on whole muscle hypertrophy [quadriceps muscle cross-sectional area (qCSA)] among nonresponders and responders to a low RT dose (single-set). We also investigated the effects of RT volume manipulation on muscle strength in these responsiveness groups. Eighty-five older individuals [41M/44F, age = 68 ± 4 yr; body mass index (BMI) = 26.4 ± 3.7 kg/m 2 ] had one leg randomly allocated to a single (1)-set and the contralateral leg allocated to four sets of unilateral knee-extension RT at 8–15 repetition maximum (RM) for 10-wk 2 days/wk. Pre- and postintervention, participants underwent magnetic resonance imaging (MRI) and unilateral knee-extension 1-RM strength testing. MRI typical error (2× TE = 3.27%) was used to classify individuals according to responsiveness patterns. n = 51 were classified as nonresponders (≤2× TE) and n = 34 as responders (>2× TE) based on pre- to postintervention change qCSA following the single-set RT protocol. Nonresponders to single-set training showed a dose response, with significant time × set interactions for qCSA and 1-RM strength, indicating greater gains in response to the higher volume prescription (time × set: P < 0.05 for both outcomes). Responders improved qCSA (time: P < 0.001), with a tendency toward higher benefit from the four sets RT protocol (time × set: P = 0.08); on the other hand, 1-RM increased similarly irrespectively of RT volume prescription (time × set: P > 0.05). Our findings support the use of higher RT volume to mitigate nonresponsiveness among older adults. NEW & NOTEWORTHY Using a within-subject unilateral design, we demonstrated that increasing resistance training (RT) volume may be a simple, effective strategy to improve muscle hypertrophy and strength gains among older adults who do not respond to low-volume RT. In addition, it could most likely be used to further improve hypertrophic outcomes in responders.